The Diagnostic Potential of Gut Microbiota-Derived Short-Chain Fatty Acids in Preeclampsia - Li, Jialin; Wang, Lin; Chen, Haimin; Yang, Zhenglun; Chen, Siqian; Wang, Jiayi; Zhou, Yuping; Xuan, Rongrong (Frontiers in Pediatrics, 2022)
Preeclampsia (PE) is a complex pregnancy-related hypertensive disorder leading to multiorgan dysfunction. It has high maternal, fetal, and neonatal morbidity and mortality rates. The study of gut microbiota and its metabolites in PE deserves further exploration. Thirty-eight pregnant women with PE and 29 healthy pregnant women in the third trimester of their pregnancy were recruited in this study. We used a targeted metabolomics approach to evaluate the short-chain fatty acids (SCFAs) in serum samples. The correlation between SCFAs and clinical characteristics was also explored. The results of mass spectrometry (MS) showed significant differences at the metabolomics level of SCFAs between the PE and healthy control. The metabolic levels of acetate, propionate, isobutyrate, and valerate were significantly increased in the PE group than in the healthy control group. In contrast, caproic acid and butyrate levels were significantly reduced. The correlation analysis showed that urea, systolic, and diastolic blood pressure levels were positively correlated with four types of SCFAs (acetic acid, propionic acid, isobutyric acid, and valeric acid) which increased in the PE group. Furthermore, the neutrophil percentage and the fetal birth weight were negatively correlated with isobutyric acid and valeric acid. In addition, the receiver operating characteristic (ROC) analysis using a generalized linear model showed that multiple SCFAs would be potential diagnostic markers for PE, with high specificity, sensitivity, and area under the curve (AUC). Among them, isobutyric acid (sensitivity: 97.4%, specificity: 100%, AUC =1.00), propionic acid (sensitivity: 86.8%, specificity: 93.3%, AUC=0.954) and acetic acid (sensitivity: 86.8%, specificity: 83.3%, AUC=0.891) depicted significantly higher diagnostic value and potential clinical applications. In summary, the results of this study indicate that SCFAs have the potential to become effective biomarkers for early screening of PE.